The inadequacies of Law on Protection of Consumer’s Rights 2010 and The Solutions for Improvement - Diep, Nguyen Trong; Ly, Nguyen Thanh (VNU Journal of Science: Legal Studies; Vol 36 No 2, 2020)
On 17 November 2010, the eighth session of the XII National Assembly passed the Law on Protection of Consumer’s rights, which took effect on July 1, 2011, set an important legal milestones that affirmed the interest of the Party and the State in protecting consumer’s rights. However, after 10 years of enforcement, some regulations of the Law on Protection of consumer’s rights 2010 are no longer in accordance with reality. Consumer relations in the context of the market economy are varied and complex have posed great challenges to the legal system to protect consumers. Through this article, the authors pointed out some inadequacies of the Law on Protection of Consumer’s rights 2010 and at the same time proposed solutions to improve the Law on Protection of Consumer’s rights 2010. Keywords: consumers, human rights, consumer relations. References:  [1] Law on Protection of Consumer rights, 2010. [2] Law on Marriage and Family, 2014. [3] Law on Product and Goods quality, 2007. [4] Law Commercial, 2005. [5] The Civil Code law, 2015. [6] Law Construction 2014. [7] Resolution No. 39/248 of April 9, 1985 of the United Nations General Assembly. [8] Nguyen Van Cuong (2013), Consumer concepts in the laws of countries and the issue of building consumer concepts in the Draft Law on Law on Protection of Consumer Rights, Institute of Legal Science, Ministry of Justice, Hanoi. [9] Nguyen Trong Diep (Lead researcher, 2015), Subject: Current mechanism to protect consumer rights in Vietnam, Science and Technology Research Project, Human Rights Center Project, National University [10] Nguyen Nhu Phat, "Current laws on consumer protection in Vietnam - status and legislative directions", presentation at the Workshop on Consumer Protection - International experiences, Situation and Prospects in Vietnam, Institute of State & Law, Ho Chi Minh City, November 16, 2009. [11] Council Directive of 25 July 1985 on the approximation of the laws, regulations and administrative provisions of the Member States concerning liability for defective products (85/374/EEC) (OJ L 210, 7.8.1985, p. 29).